Legal Issues Concerning Surrogacy in Uganda: Taking a Leap from the United Kingdomd - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Eregbuonye, Obieshi; Okpoko, Mercy Osemudiame; Ekpenisi, Collins (Fakultas Hukum Universitas Islam Malang, 2025)
The practice of surrogacy in Uganda has several legal issues and implications. Therefore, this study aims to analyze the legal issues and implications related to surrogacy in Uganda and make comparisons with the United Kingdom. In this case, the study was conducted using a doctrinal research method, relying on primary and secondary research materials. This study found the following: legislation on surrogacy is still being developed by the Ugandan government, and existing laws do not directly regulate surrogacy, which essentially creates legal loopholes and legal vacuums. In addition, this study found that UK law appears to adequately address issues related to surrogacy. This study concludes and recommends that the Ugandan government needs to accelerate the enactment of legislation on surrogacy to address relevant issues in the future, such as the commodification of women's bodies, parental rights, the best interests of the child, and so on.